Structural and Electronic Reconstructions at the LaAlO3/SrTiO3 Interface. (5th February 2013) - Salluzzo, M.; Gariglio, S.; Torrelles, X.; Ristic, Z.; Di Capua, R.; Drnec, J.; Sala, M. Moretti; Ghiringhelli, G.; Felici, R.; Brookes, N. B.
<x xml:space="preserve">Abstract</x> A full understanding of the mechanism of the formation of a two‐dimensional electron gas (2DEG) at the interface between insulating LaAlO3 (LAO) thin films and bulk SrTiO3 (STO) crystals is a prerequisite for the full exploitation of this class of materials. Here, by using a combination of advanced X‐ray synchrotron‐based spectroscopic and structural measurements, it is shown that a structural and electronic reconstruction of the interface occurs before the realization of the 2DEG. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>